Interconnecting DC busses of solar/wind based power supply system - Seo, Yue Siang. (2013)
Increasing energy demands have contributed to global warming and led to fossil fuels depleting at an alarming rate. Therefore, researchers have looked to alternative sources of energy to meet these demands, and some of the more established ones include solar and wind energy. These renewable energy systems require an energy storage device to store surplus power and deliver additional power when required. Also, they are able to regulate the voltage between the source and the output and ensure power stability and quality. Before that, the energy storage system is required to be at the same potential level as the DC bus of the renewable system. As such, the focus of this project will fall mainly on the design and modeling of the energy storage system, and implemented into a wind energy conversion system.